Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00417-014-2773-5
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of retinal nerve fiber layer and macular ganglion cell–inner plexiform layer with spectral-domain optical coherence tomography in patients with optic nerve head drusen

Abstract: Both RNFL and GCIPL analysis reveal significant thinning in eyes with ONHD directly correlated with drusen severity. In buried ONHD, the abnormality rate was significantly higher with GCIPL compared to RNFL evaluation, suggesting that GCIPL analysis might be an early structural indicator of neuronal loss in the setting of thickened RNFL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…We also show that ONH drusen is associated with changes to RGC dendrites, cell bodies and the unmyelinated portion of RGC axons. The latter findings have previously been demonstrated using optical coherence tomography . Collectively, the findings of our study suggest that disc drusen induces alterations to all four compartments of the RGC, similar to glaucoma.…”
supporting
confidence: 88%
“…We also show that ONH drusen is associated with changes to RGC dendrites, cell bodies and the unmyelinated portion of RGC axons. The latter findings have previously been demonstrated using optical coherence tomography . Collectively, the findings of our study suggest that disc drusen induces alterations to all four compartments of the RGC, similar to glaucoma.…”
supporting
confidence: 88%
“…A study by Casado et al (2014) found macular RNFL decrease in patients with ODD when compared to control subjects. The study further found a higher percentage of abnormal thinning associated with more crowded discs.…”
Section: Oct-measured Rnfl Thicknessmentioning
confidence: 97%
“…62 A new OCT parameter, macular ganglion cell-inner plexiform layer (GCIPL) thickness, may show thinning earlier than the RNFL in buried optic disc drusen in both children and adults. 25; 163 Some authors have sought to use OCT RNFL thickness to distinguish between optic disc drusen and true disc edema, in which RNFL thickness may be higher, especially nasally; 11; 88; 181 however, the degree of RNFL thickening in true disc edema may depend on the severity of edema, and thickness may not differ significantly between mild optic disc edema and pseudopapilledema. 92 …”
Section: Diagnostic Testingmentioning
confidence: 99%